BENTUK CAYLEY COLOR DIGRAPH GRUP SIKLIK G DENGAN ORDER n - M. Ariq Zainurrifqi; Mohammad Agung; Indriati Nurul Hidayah (UNIVERSITAS NEGERI MALANG, 2022)
Let G be a cyclic group with set of generators . Let G with color xi is a digraph with vertices elements of and there is an arrow from to if . In this artcle, we find the Cayley color digraph of a cylic group of order . We also proved the existence of Hamiltonian cycle of the graph